2008
DOI: 10.1007/s11274-008-9749-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of agro-wastes by solid-state fermentation: enhanced antioxidant activities and nutritional qualities

Abstract: Solid substrate fermentations of some agrowastes, namely cocoa pod husk (CPH), cassava peel (CP), and palm kernel cake (PKC) were carried out for the production of fructosyltransferase (FTase) by a newly isolated fungal strain Rhizopus stolonifer LAU 07. The fermented substrate were studied for improved nutritional quality by determining the crude protein, crude fibre, ash and lipid contents, and antioxidant activities. The cyanide content of cassava peels was also determined. Some levels of valueaddition occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 32 publications
4
46
2
6
Order By: Relevance
“…As fermentation of okara increased, the fibre content increased. This was not in agreement to the findings of Lateef et al (2008) which showed that fermentation of okara with yeast decreased its crude fibre content. Sample UFAC had a fibre content of 2.49 % which was close to the findings of FAO (1998) and Ugwuona et al (2012) which was 3.3 and 1.86 % respectively.…”
Section: Proximate Composition Of the Flours Prepared From Acha And Fcontrasting
confidence: 98%
See 1 more Smart Citation
“…As fermentation of okara increased, the fibre content increased. This was not in agreement to the findings of Lateef et al (2008) which showed that fermentation of okara with yeast decreased its crude fibre content. Sample UFAC had a fibre content of 2.49 % which was close to the findings of FAO (1998) and Ugwuona et al (2012) which was 3.3 and 1.86 % respectively.…”
Section: Proximate Composition Of the Flours Prepared From Acha And Fcontrasting
confidence: 98%
“…This agreed to the research of Rashad et al (2011) which revealed that fermentation of okara decreased the fat content. Previous studies have shown reduction in the lipid content of different substrates fermented with different microorganisms (Das and Weeks 1979; Iluyemi et al 2006;Lateef et al 2008). They attributed that to the accumulation of lipids by the fungal strains and during fungal processing, some lipolytic strains assimilate lipids from substrates for biomass production leading to a general reduction of the overall lipid content of the substrate.…”
Section: Proximate Composition Of the Flours Prepared From Acha And Fmentioning
confidence: 96%
“…The cellulose level of PKC was reduced from 28.3% to 12.1% through fermentation with Trichoderma longibrachiatum, and the hemicellulose content decreased from 37.0% to 19.0% when fermented with A. niger (Iluyemi et al 2006). A study conducted by Lateef et al (2008) also showed the positive effect of fungal treatment, where a reduction of 44.5% of crude fibre in PKC was observed after 5 d of fermentation using Rhizopus stolonifer LAU 07.…”
Section: Introductionmentioning
confidence: 91%
“…Pengolahan KBK secara biologis atau fermentasi telah banyak dilakukan dengan menggunakan fermentor komersial seperti EM4, urea, BIOFIT dan atau menggunakan berbagai ragi (Rhizopus stolonifer LAU 07) untuk meningkatkan kandungan protein menjadi 16% (Lateef et al, 2008), dengan menggunakan Aspergillus spp, untuk menurunkan serat KBK (jumlah serat kasar, NDF, ADF masing -masing 33,00, 55,79 dan 44,29%) (Alemawor et al, 2009), dan menggunakan Aspergillus oryzae untuk meningkatkan protein kasar KBK sebesar 8,74% (Munier, 2009). Kulit buah kakao fermentasi diharapkan dapat dimanfaatkan oleh ternak khususnya sapi Bali yang mempunyai keunggulan dibanding jenis sapi lainnya dalam pemanfaatan pakan berkualitas rendah (Anonimus, 2015).…”
Section: Pendahuluanunclassified